Novel Tuning Scheme for Integrated Continuous Time Filter - Ilse S. Noerbambang; Hiroaki Kunieda; Samaun Samadikun (Journal of Mathematical and Fundamental Sciences, 2001)
In integrated continuous times (C.T.) filters, automatic tuning is very important, because the filter coefficients are very sensitive to device parameters. In this paper, novel tuning scheme for the integrated C.T. hand pass biquad filter is presented. This tuning scheme is used to tune the center of frequency (f0) of a band pass biquad filter which is 550 KHz. The bandwith of this filter is 535 KHz and  the quality factor Q  is equal to one. This filter consists of four CMOS  operational transconductance amplifier (OTA) and two capacitors. The tuning scheme is realized with CMOS OTAs, a CMOS four quadrant analog multiplier with voltage output, a low pass filter and a DC amplifier. By varying the capacitor values of the band pass biquad filter 40% in both direction from the nominal value and varying the temperature from -100°C to 50°C, the center frequency of the filter remain constant at 550 KHz. It is simulated using SPICE software and operates with power supply voltages of ±5 V. Simulated results are presented and discussed.